The relationship between linguistic knowledge types and inflectional output - Mohammad Lotfie, Maskanah; Salleh, Nurul Aadilah (2014)
Acquiring the morphology of the tense-aspect system of English is challenging to second language learners due to the multifaceted nature of temporal indicators. Acquisitional attempts may also be complex because of the absence of parallel indicators in the mother tongue and the types of linguistic knowledge that users have. This paper presents a discussion on Malay-English differences in temporal markers. It also reports an investigation on the types of linguistic knowledge that language learners have and their relationship with the production of past-time inflections [-en] and [-ed]. Seventy two tertiary level students who used English as a second language participated in the study. Data were collected using three instruments and they were a grammaticality judgment test (GJT), a metalinguistic knowledge test (MKT) and a written production test (WPT). Analysed data provide evidence of the correlation between explicit and implicit knowledge and target item output. Qualitative analysis of WPT indicates consistent usage of [–ed] inflection but not [–en]. The findings from the study should enhance the theoretical understanding of the role of linguistic knowledge on the development of learners’ inflectional morphology. The outcome should also inform and update language practitioners of specific pedagogical issues that need to be considered in ensuring sound language instructional practices.